(untitled) (Лучшие интеллектуальные исследования, 2025)
This article examines the transformative impact of digital technologies on the tourism industry. It explores how innovations such as online booking platforms, virtual reality, artificial intelligence, and mobile applications have reshaped travel planning, customer experience, and service delivery. The article highlights the benefits of digitalization, including increased accessibility, personalized services, and enhanced marketing opportunities for tourism businesses. Additionally, it discusses challenges such as data privacy concerns, the digital divide, and the need for continual technological adaptation. Special attention is given to the growing role of digital tools in Uzbekistan’s tourism sector, emphasizing how technology can boost competitiveness, improve visitor engagement, and support sustainable tourism development. The article concludes with recommendations for stakeholders to leverage digital advancements while addressing potential risks.